Assessing the sustainability impacts of food sharing initiatives: User testing The Toolshed SIA - Davies, Anna (My University, 2022)
The food system is unsustainable and requires reconfiguration, however more data is required to assess the impacts of action which might contribute to a more sustainable food future. Responding to this, extensive research with food sharing initiatives—activities which have been flagged for their potential sustainability credentials—led to the co-design of an online sustainability impact assessment (SIA) tool to support food sharing initiatives to asses and evidence their sustainability impacts. This paper reports on the initial user testing of the resulting online tool: The Toolshed which forms the indicator based SIA element of the SHARE IT platform. Feedback gathered from the initiatives testing the tool are analyzed and summaries of their reported impacts detailed. This analysis confirms the need for the tool, the relevance of the indicators included and the value of SIA reports for internal reflection and external communication. Nonetheless, challenges remain in relation to resourcing the practice of SIA reporting. We conclude with a plan for expanding engagement with The Toolshed and the wider SHARE IT platform.
PUBLISHED
Keywords: sustainability impact assessment; food sharing; online toolkit; user testing; food system; sustainability reporting; Smart & Sustainable Planet